ปัจจัยเชิงสาเหตุที่ส่งผลต่อการเป็นพลเมืองดีตามวิถีประชาธิปไตยของนักเรียนชั้นมัธยมศึกษาตอนปลายโรงเรียนในสังกัดองค์การบริหารส่วนจังหวัดนครราชสีมา - สาคุณ, นงค์รัก; ทานอก, สมเกียรติ (Ph.D. in Social Sciences Journal, 2017)
การวิจัยครั้งนี้มีวัตถุประสงค์ 1) เพื่อศึกษาระดับการเป็นพลเมืองดีตามวิถีประชาธิปไตยของนักเรียนในระดับชั้นมัธยมศึกษาตอนปลาย โรงเรียนในสังกัดองค์การบริหารส่วนจังหวัดนครราชสีมา 2) เพื่อศึกษาปัจจัยที่ส่งผลต่อการเป็นพลเมืองดีตามวิถีประชาธิปไตยของนักเรียนในระดับชั้นมัธยมศึกษาตอนปลาย โรงเรียนในสังกัดองค์การบริหารส่วนจังหวัดนครราชสีมา และ 3) เพื่อพัฒนา และตรวจสอบความสอดคล้องโมเดลปัจจัยเชิงสาเหตุที่ส่งผลต่อการเป็นพลเมืองดีตามวิถีประชาธิปไตยของนักเรียนในระดับชั้นมัธยมศึกษาตอนปลาย โรงเรียนในสังกัดองค์การบริหารส่วนจังหวัดนครราชสีมา ที่สร้างขึ้นกับผลการวิเคราะห์ข้อมูลเชิงประจักษ์ กลุ่มตัวอย่างที่ใช้ในการวิจัยในครั้งนี้ เป็นนักเรียนในระดับชั้นมัธยมศึกษาตอนปลาย ปีการศึกษา 2558 สังกัดองค์การบริหารส่วนจังหวัดนครราชสีมา จำนวน 584 คน โดยวิธีการสุ่มแบบหลายขั้นตอน (Multi-Stage Random Sampling) เครื่องมือที่ใช้ในการรวบรวมข้อมูล เป็นแบบสอบถามเกี่ยวกับปัจจัยเชิงสาเหตุที่ส่งผลต่อการเป็นพลเมืองดีตามวิถีประชาธิปไตย ของนักเรียนชั้นมัธยมศึกษาตอนปลาย โรงเรียนในสังกัดองค์การบริหารส่วนจังหวัดนครราชสีมา สถิติที่ใช้ในการวิเคราะห์ข้อมูลเบื้องต้นของตัวแปรได้แก่ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน สัมประสิทธิ์สหสัมพันธ์เพียร์สัน และตรวจสอบความสอดคล้องของรูปแบบความสัมพันธ์เชิงสาเหตุที่พัฒนาขึ้นกับข้อมูลเชิงประจักษ์ด้วยโปรแกรมลีสเรล ผลการวิจัยพบว่า 1. ปัจจัยเชิงสาเหตุที่ส่งผลต่อการเป็นพลเมืองดีตามวิถีประชาธิปไตยของนักเรียน ชั้นมัธยมศึกษา ตอนปลาย โรงเรียนในสังกัดองค์การบริหารส่วนจังหวัดนครราชสีมา มีทั้งหมด 5 ปัจจัย ได้แก่ การอบรมเลี้ยงดู ความสัมพันธ์ระหว่างนักเรียนกับเพื่อน ลักษณะมุ่งอนาคต ความสัมพันธ์ระหว่างนักเรียนกับครู และทักษะทางสังคม มีค่าเฉลี่ยอยู่ในระดับมากทุกด้าน โดยด้านที่มีค่าเฉลี่ยสูงสุด 3 อันดับแรก คือการอบรมเลี้ยงดู รองลงมาคือความสัมพันธ์ระหว่างนักเรียนกับครู และทักษะทางสังคม ส่วนตัวแปรที่มีค่าเฉลี่ยต่ำที่สุดคือ ความสัมพันธ์ระหว่างนักเรียนกับเพื่อน 2. โมเดลปัจจัยเชิงสาเหตุที่ส่งผลต่อการเป็นพลเมืองดีตามวิถีประชาธิปไตย ของนักเรียนชั้นมัธยม ศึกษาตอนปลาย โรงเรียนในสังกัดองค์การบริหารส่วนจังหวัดนครราชสีมา มีความสอดคล้องกับข้อมูลเชิงประจักษ์ มีค่า c2 = 23.82, df = 71, P = 1.000, GFI = 1.00, AGFI = 0.99 และ RMR = 0.010 3. ตัวแปรการเป็นพลเมืองดีตามวิถีประชาธิปไตย ของนักเรียนชั้นมัธยมศึกษาตอนปลายได้รับอิทธิพลทางตรงจากการอบรมเลี้ยงดูสูงสุด รองลงมาคือ ทักษะทางสังคม ความสัมพันธ์ระหว่างนักเรียนกับครู ความสัมพันธ์ระหว่างนักเรียนกับเพื่อน และลักษณะมุ่งอนาคต ตามลำดับ และได้รับอิทธิพลทางอ้อมจากการอบรมเลี้ยงดูสูงสุด โดยส่งผ่านมาทางความสัมพันธ์ระหว่างนักเรียนกับครู และทักษะทางสังคม รองลงมา คือความสัมพันธ์ระหว่างนักเรียนกับเพื่อนโดยส่งผ่านทักษะทางสังคม และตัวแปรที่มีอิทธิพลทางอ้อมต่อการเป็นพลเมืองดีตามวิถีประชาธิปไตย อันดับที่สาม คือความสัมพันธ์ระหว่างนักเรียนกับครูโดยส่งผ่าน ทักษะทางสังคม ตัวแปรที่มีอิทธิพลทางอ้อมต่อการเป็นพลเมืองดีตามวิถีประชาธิปไตย อันดับที่สี่ คือลักษณะมุ่งอนาคตโดยส่งผ่านมาทางทักษะทางสังคม The Causal Factors that lead to be the Good-Citizens based on Democratic Way of The High School Students in The Subordinated School in Provincial Administrative Organization of Nakhon Ratchasima The objectives of the study were: 1) To examine the level of being the good-citizens based on democratic way of high school students in the subordinated school in Provincial Administrative Organization of Nakhon Ratchasima 2) To examine the factors that lead to be the good-citizens based on democratic way of high school students in the subordinated school in Provincial Administrative Organization of Nakhon Ratchasima and 3) To develop and investigate the relative causal factor model that lead to be the good-citizens based on democratic way of high school students in the subordinated school in Provincial Administrative Organization of Nakhon Ratchasima, created by the analysis result-based practice. 584 student samples were selected from the High School students in the subordinated school in Provincial Administrative Organization of Nakhon Ratchasima in 2015 with Multi-Stage Random Sampling technique. A tool for collecting the data was Causal Factors questionnaire that leads to be the good-citizens based on democratic way of high school students in the subordinated school in Provincial Administrative Organization of Nakhon Ratchasima. The statics for initial analysis of variable were mean, standard deviation, Pearson's correlation and verifying the consistency of causal relative developed by the data-based practice from LISREL Version 8.72 program. The results of the study were: 1. The causal factors that led to be the good-citizens based on democratic way of high school students in the subordinated school in Provincial Administrative Organization of Nakhon Ratchasima contained main five factors: 1) rearing, 2) relationship between student and friend, 3) future-based characteristics, 4) relationship between student and teacher and 5) social skills. There’re high mean in every factors, the three highest variables were rearing, relationship between student and teacher and social skill. The lowest variable was relationship between student and friend. 2.The causal model that led to be the good-citizens based on democratic way of high school students in the subordinated school in Provincial Administrative Organization of Nakhon Ratchasima showed that relative data-based practice contained c2 = 23.82, df = 71, P = 1.000, GFI = 1.00, AGFI = 0.99 and RMR = 0.010 3.The variable of being the good-citizens based on democratic way of high school students was directly influenced from rearing, social skill, relationship between student and teacher, relationship between student and friend and future-based characteristics, respectively. Moreover, there’re four indirect influences for being the good-citizens based on democratic way; 1) the rearing passing through the relationship between student and teacher including the social skill, 2) the relationship between student and friend passing through the social skill, 3) the relationship between student and teacher passing through the social skill and 4) the future-based characteristic passing through the social skill.